Biopharma Processing and Delivery / An In-Depth Focus that Includes Bioproduction Monitoring Antibodies and the Manufacture of Robust Biologic Drug Products - Stones Mike (Russel Publishing Ltd, 2018)
The Path to Clinic: Recent Developments in Turning Promising Compounds Into Drug Candidates, Reviewing the Latest Trends in Pharmaceutical Microbiology and Their Implications, Track and Trace Roundtable Debate Features the Views of Five Industry Leaders on this Topic.